2011
DOI: 10.1002/pola.24602
|View full text |Cite
|
Sign up to set email alerts
|

Poly(siloxane‐urethane) crosslinked structures obtained by sol‐gel technique

Abstract: Poly(siloxane‐urethane) crosslinked structures were prepared from isophorone diisocyanate, α,ω‐bis(hydroxybutyl)oligodimethylsiloxane and a new hybrid diol containing hydrolysable SiOC2H5 groups besides OH groups. The latest was synthesized by the acid‐catalyzed reaction between 1,3‐bis(3‐glycidoxypropyl)tetramethyldisiloxane and 3‐aminopropyltriethoxysilane. The formations of the urethane groups along the polymer backbone as well as the formation of the silica domains were first confirmed by the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 47 publications
1
29
1
Order By: Relevance
“…5b). When compared with literature data, it can be observed that rubbery plateau modulus of the investigated PU networks are higher than values determined for other type of crosslinked poly(siloxaneurethane)s [30], as well as for PUs synthesized with different macrodiol and crosslinked with Boltorn® HBP [9].…”
Section: Dynamic Mechanical Thermal Analysis Of Polyurethane Networkcontrasting
confidence: 53%
“…5b). When compared with literature data, it can be observed that rubbery plateau modulus of the investigated PU networks are higher than values determined for other type of crosslinked poly(siloxaneurethane)s [30], as well as for PUs synthesized with different macrodiol and crosslinked with Boltorn® HBP [9].…”
Section: Dynamic Mechanical Thermal Analysis Of Polyurethane Networkcontrasting
confidence: 53%
“…The EDX analysis, performed to identify the type of the atoms present in the polyurethane samples at a depth of 100-1000 nm from the surface, 22 confirmed the presence of all expected elements (C, O, Si and N). The results obtained from EDX analysis are displayed in Fig.…”
Section: Investigation Of Morphology Of the Synthesized Polyurethane mentioning
confidence: 73%
“…This observation indicates that cohesion and stability of the PU network are not destroyed under the investigated experimental conditions. 31 In addition, Figure 4 shows that during the glass transition of the soft segment, the G′ of the synthesized PUs slightly decreases, while in the glass transition region of the hard segments G′ rapidly decreases as a consequence of the increased mobility of the chains. On the other hand, the presence of the chemical cross-links restricts the flow of the polymer in the rubbery plateau (around 130°C…”
Section: Resultsmentioning
confidence: 96%